2010
DOI: 10.1086/651680
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease a Decade after Pneumococcal Conjugate Vaccine Use in an American Indian Population at High Risk for Disease

Abstract: Background. Before 7-valent pneumococcal conjugate vaccine (PCV7) introduction, invasive pneumococcal disease (IPD) rates among Navajo were several-fold those of the general US population. Only 50% of IPD cases in children involved PCV7 serotypes.Methods. We conducted active, population-based surveillance for IPD for the period 1995-2006. We documented case characteristics and serotyped the isolates. Results. Over 12-year period, we identified 1508 IPD cases, 447 of which occurred in children aged !5 years. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 16 publications
(22 reference statements)
1
52
0
Order By: Relevance
“…The serotype distribution of patients identified by culture reported in this study is similar to what other authors have found [17,18]. The most prevalent serotype in patients identified by culture is serotype 1, as in other regions of Spain and in Portugal.…”
Section: Discussionsupporting
confidence: 89%
“…The serotype distribution of patients identified by culture reported in this study is similar to what other authors have found [17,18]. The most prevalent serotype in patients identified by culture is serotype 1, as in other regions of Spain and in Portugal.…”
Section: Discussionsupporting
confidence: 89%
“…In the United States, these rate increases are small relative to the major decreases in vaccine serotype disease that have been achieved. Among certain Native American populations with high underlying rates of pneumococcal disease, the magnitude of the nonvaccine serotype replacement disease has ranged from small among Navajo and White Mountain Apache populations [5,6] to large among Alaska Natives [4]. The broad diversity of pneumococcal serotypes capable of causing disease has fueled development of second-generation pneumococcal conjugate vaccines with increased valency (ie, broader serotype coverage).…”
mentioning
confidence: 99%
“…The issues of novel serotype emergence and effectiveness of new PCVs are particularly important for some Native American communities, where disproportionately high rates of pneumococcal disease and carriage have persisted in spite of high levels of immunization coverage [4][5][6]. Over the past 12 years, we have conducted a number of population-based studies of pneumococci and established a repository of isolates, collected in the context of a large-scale, cluster-randomized vaccine efficacy trial [13], ongoing laboratory-based active surveillance for invasive disease [6], and a number of household-based studies of nasopharyngeal carriage [14][15][16].…”
mentioning
confidence: 99%
“…[18] In the Navajo population, between 1995 and 2006, in an active surveillance system which included 1508 cases of IPD the total number of cases decreased from 67 in 1995-1997 to 51 cases in the years following PCV7 introduction. [20] There was no change in the nonvaccine type (NVT) in children in the post vaccine era. Rates increased for serotypes 1, 3, 5, 7F, 19A, 18B.…”
Section: The Effect Of Pcv7 On Invasive Diseasementioning
confidence: 99%
“…In infants under the age of 2 months no cases with serotype included in the PCV7 was reported with no replacement by NVT disease. [20] A combined study of four European countries was done after PCV7 introduction in Europe. [21] Different countries have implemented vaccination in various time periods, but all consider the 7 serotypes contained in the vaccine as being responsible for 68% to 77% of IPD in children under 5 years of age.…”
Section: The Effect Of Pcv7 On Invasive Diseasementioning
confidence: 99%